Role of power Doppler and gray-scale ultrasound of the median nerve in the evaluation of carpal tunnel syndrome: A comparative analysis between sonographic and surgical measurements of the median nerve - Mohammad Farooq Mir; Shazia Bashir; Hilal Ahmad Lone; Tahir Ahmad Dar (Asian Journal of Medical Sciences, 2022)
Background: Carpal tunnel syndrome (CTS) is the prevalent cause of pain, numbness, tingling, and weakness. It is known that whenever the median nerve, a major peripheral nerve of the upper limb, originating from the forearm into the palm of the hand, becomes pressed or squeezed at the wrist, it leads to a condition commonly known as CTS. Aims and Objectives: The present study has been objectively conducted to assess the role of grey scale and power Doppler ultrasound of the median nerve at the wrist in evaluating CTS. The comparative analysis between USG findings and surgical findings of median nerve in CTS will also be made. Materials and Methods: The present prospective study has been conducted at the SKIMS-MC, Srinagar for a period of 6 months from January 2022 to June 2022 in the Department of Radio diagnosis and Imaging in association with the Department of Orthopedics. A total of 30 patients have been included in the study. The cases were referred from Department of Orthopedics with clinically characterized CTS. Results: Out of total 30 patients; 03 (10%) were males and 27 (90%) were females with a male to female ratio of 1:9. We observe that vascularity of median nerve was present in (56.7%) and absent in (43.3%) patients. The median nerve thinning and indentation were reflected by (80%) patients and the same was absent among (20%) patients, we did not find any agreement between surgical and sonographic parameters with the mean difference of 2.527 mm between sonographic and intraoperative perimeters, the difference was statistically significant (P<0.001, CI 95%). Conclusion: The present study demonstrated that ultrasonography aided with power Doppler precisely detected CTS cases. Evidently, we find a significant difference between surgical and sonographic parameters with the mean difference of 2.527 mm between sonographic and intraoperative perimeters.